Hypothetico-deductive learning cycle and biology student conceptual understanding, self-efficacy and task value - Medina, Rhoel C. (2006)
This study aimed to compare the effectiveness of the Hypothetico-Deductive Learning Cycle (HDLC) against the conventional method of teaching in improving second year biology students' conceptual self-understanding, self-efficacy, and task value beliefs. It used the pretest-posttest non-equivalent quasi-experimental design with a sample consisting of two sections of second year high school students at Cainta Catholic College. The Conceptual Understanding Test, Self-efficacy and Task Value Scale, and the VARK inventory were used to gather data. From the findings of the study, it was concluded that the HDLC approach can be effective in eliminating certain alternative conceptions particularly those that are not well-entrenched. However, the HDLC is only slightly better than the conventional approach in improving self-efficacy but is more effective in maintaining and improving students' level of task value.
Thesis (M.A. Biology Education)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Philippines -- Cainta (Rizal); Self-efficacy.; High school students -- Philippines -- Cainta (Rizal)